ANALYSIS TIME STUDY AND TAKT TIME IN THE PRODUCT LOADING PROCESS - Mochammad Amru Nail Suherman; Tedjo Sukmono (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: The purpose of this study is to determine the standard delivery process time and also determine the speed of workers. Method: The results of observations in this study will be processed using the time study method, which is a process used to determine how long it takes when carrying out a job or task with the aim of improving performance. This method will then be compared with the takt time method, which is a method of determining decisions regarding production capacity through the production system within a predetermined time. Results: The results used as the best time determination using the standard time of 47.01 minutes. Then, the takt time result of 21.6 minutes is used as a simulation of a more efficient roll loading process planning proposal. Novelty: This research highlights the problem of differences in roll loading process time between morning, afternoon, and night shifts, resulting in a 74.7% decrease in shipping capacity. The study introduces a comparison between time study and takt time methods to improve process efficiency and optimize shipping capacity.